Physokermes hemicryphus (Dalman) a fir scale insect useful to apiculture in Greece - Santas, L.A. (ENTOMOLOGIA HELLENICA, 1988)
Physokermes hemicryphus (Dalman) is an important honeydew producing scale insect useful to apiculture. It lives mainly on Abies cephalonica Loud. and to a lesser degree on Abies borisii regis Mattf. These fir trees exist in most fir forests of Greece. It has one generation per year. Overwintering takes place in the second instar nymph. The female overwinters under the bud scales of the forks of the fir host and the male on the needles. Adults appear in spring and crawlers in July. In August the population consists mainly of first instar nymphs. The second instar nymphs start to appear in August and by late October the whole population is at the second nymphal instar, which is the overwintering one. The insect occurs in the fir forests of Greece every year but its population level fluctuates, due to weather conditions and biological factors (parasites, predators). The coexistence on the same host plant of P. hemicryphus with the scale Eulecanium sericeum (Lindiger) and the aphid Milldams abietinus (Koch) prevents the visit of honeybees to fir trees. On the other hand it favours the augmentation of the P. hemicryphus population. Four parasites were found, from which the Encyrtidae Pseudorhopus testaceus (Razz.) and Microterus lunatus (Dalman), are recorded for the first time in Greek fauna.